Management of a patient at high risk of type 2 diabetes - Howells, Lara (London J Prim Care (Abingdon), 2016)
Rates of type 2 diabetes mellitus have risen rapidly over the past three to four decades. This article describes a typical patient presenting with intermediate hyperglycaemia in primary care. We suggest the appropriate action to reduce the risk of diabetes developing. Population-level preventive interventions, and adequate recognition and early management of those at risk of developing diabetes, could mitigate the impact of this evolving health epidemic.